Źródła zagrożeń bezpieczeństwa społecznego – rodzina dysfunkcjonalna - Wróbel-Delegacz, Wioletta (Doctrina. Studia społeczno-polityczne, 2019)
Family is a basic social group influencing the shaping up of a young citizen’s personality, attitudes and values. Healthy, properly functioning one gives its members the sense of security and results in proper educational process including the education for security. Dysfunctional family presented as one of social pathologies affects the sense of personal security of its members and may pose the threat to social security. The research carried out by Alicja Keplinger in 2007 resulted in the statement that respondents consider social pathologies the main threat to national security, whereas natural calamities took the second place. The article is divided into two parts, in the first part it is explained what the national security is, and its role in the national security is depicted. In the second part the problem of family is discussed in the area of its functionality and dysfunctionality, as well as the significance of the threat to national and social security this phenomenon poses, which is frequently only mentioned in the literature of the subject where contemporary social threats are named. On the basis of the literature analyses and my own experience one can claim that frequently one pathology is the source of another. Family dysfunctionality is indicated as one of the reasons for many other pathologies, such as crime, drug addiction or alcoholism, which constitute a threat to the citizens security. For example, the fact that in the research conducted in 2013 by CBOS concerning the sense of security, in this case related to crime, 44 per cent of respondents feel anxiety and security threat. Besides the fact that dysfunctional family poses a threat to the citizens’ security of the whole society through triggering negative and antisocial behavior, it also poses a threat by, for instance, not fulfilling or limited fulfillment of procreation functions which endangers the continuity of the society, its identity and threatens social benefits (financial provision) for the citizens of a given country. According to GUS the birth rate in 2010 amounted to 34.8, in 2011 – 12.9 and in 2012 only 1.5. The article is aimed to present how important but scarcely depicted the problem of family dysfunctionality is, as a serious threat to social security.